2003
DOI: 10.1002/ijc.10957
|View full text |Cite
|
Sign up to set email alerts
|

HSD17B1 and CYP17 polymorphisms and breast cancer risk among Chinese women in Singapore

Abstract: Reasons for the recent trend of increasing breast cancer incidence among Chinese and other Asian women are not well understood. Endogenous estrogen levels are strongly associated with breast cancer risk and its determinants include both genetic and lifestyle factors. We conducted a nested case-control study to investigate, within the Singapore Chinese Health Study Cohort, the relationships between polymorphisms in 2 genes involved in estrogen metabolism, CYP17 and HSD17B1, and the risk of breast cancer. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
3

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 27 publications
(39 reference statements)
4
63
3
Order By: Relevance
“…Due to individual differences in exposure to factors modifying genetic levels of E 2 , however, a relationship between CYP17 genetic polymorphism and risk of breast cancer may not be detectable. Several studies tested the relationship between CYP17 polymorphism and risk of breast cancer (23,37,42,(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59), but results are conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…Due to individual differences in exposure to factors modifying genetic levels of E 2 , however, a relationship between CYP17 genetic polymorphism and risk of breast cancer may not be detectable. Several studies tested the relationship between CYP17 polymorphism and risk of breast cancer (23,37,42,(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59), but results are conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have evaluated whether germline variation in HSD17B1 is associated with breast or endometrial cancer [33][34][35][36], this is the first large prospective study to assess HSD17B1 in relation to prostate cancer among men from several ethnicities. Table 1 shows demographic and other characteristics of cases and controls from the seven cohorts.…”
Section: Synopsismentioning
confidence: 99%
“…In a study conducted in Singapore, a 1.8-fold increased risk of breast cancer was found for postmenopausal Chinese women with the AA genotype (15). However, in a pooled analysis of 5,370 cases and 7,480 matched controls from the Breast and Prostate Cancer Cohort Consortium, the majority of whom were Caucasian, none of the common HSD17B1 haplotypes defined by four haplotype-tagging single nucleotide polymorphisms (including rs605059) were associated with breast cancer risk (21).…”
Section: Introductionmentioning
confidence: 99%
“…Although most studies have found no overall relationship (9,10), some studies of non-Caucasian women have found breast cancer risk associated with this polymorphism to vary by age or menopausal status (11)(12)(13)(14), body mass index (BMI; ref. 13), and age at first birth and parity combined (15). Furthermore, although in vitro data have not confirmed that the additional Sp-1 binding site leads to increased gene transcription (16), higher endogenous levels of estrogens and androgens have been reported in carriers (versus noncarriers) of the A2 allele (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation